1998
DOI: 10.1002/masy.19981290105
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of polymeric hydrocarbons

Abstract: Although polymeric hydrocarbons (PCH) carry no functions, they can be modified in many ways. Unsaturated PCH undergo addition reactions as hydrogenation, halogenation, epoxidation and thiol addition. Saturated PCH can be substituted with various functions, notably halogen and chlorosulfonyl groups. All PCH can be modified, by a grafting mechanism, with functional monomers as maleic anhydride. Some modified PCH play a major role in multiphase systems as blends, rubber‐modified thermoplastics and thermoplastic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In the first step, P(Eco-GMA) was converted into ATRP macroinitiators by the addition reaction of ClAA and BrIBA to the epoxy ring of the GMA units, catalyzed by TBAH. 1 H NMR analysis of the macroinitiators showed that anionic polymerization of the oxirane rings and double additions to the epoxy ring occurred as side reactions. The pendantfunctionalized polyolefins were used to initiate the ATRP of styrene and methyl methacrylate to produce graft copolymers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first step, P(Eco-GMA) was converted into ATRP macroinitiators by the addition reaction of ClAA and BrIBA to the epoxy ring of the GMA units, catalyzed by TBAH. 1 H NMR analysis of the macroinitiators showed that anionic polymerization of the oxirane rings and double additions to the epoxy ring occurred as side reactions. The pendantfunctionalized polyolefins were used to initiate the ATRP of styrene and methyl methacrylate to produce graft copolymers.…”
Section: Discussionmentioning
confidence: 99%
“…However, as polyolefins are incompatible with almost all other polymers due to their low surface energy, compatibilizing agents are necessary in order to avoid macrophase separation. 1 The compatibilizers are usually block or graft copolymers, which contain a polyolefin segment. Free radical graft polymerization is the most used technique to prepare compatibilizing agents starting from PE, PP, or ethylene-propylene rubber (EPDM).…”
Section: Introductionmentioning
confidence: 99%